1992
DOI: 10.1159/000175807
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Cardiac Enlargement and Congestive Heart Failure Development after Acute Myocardial Infarction

Abstract: For 3 months, we followed up 40 patients with acute myocardial infarction, 20 were randomly assigned to treatment with captopril and 20 to placebo, to elucidate mechanisms inducing left ventricular volume enlargement and development of congestive heart failure. Echocardiographic follow-up could be obtained in 28 patients, 11 of whom showed more than a 10% increase in left ventricular systolic and/or diastolic volumes (captopril n = 3/15, placebo n = 8/13, p = 0.05). Volume increase was significantly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…19 In fact, the degree of left ventricular remodeling is regarded as an important factor in determining the prognosis of MI. [20][21][22] Seals et al reported that left ventricular dilation occurs within hours of AMI in both inferior and anterior AMI, but is more marked in the latter because it has usually more extensive myocardial damage compared with inferior AMI. 23 Moreover, considerable attention has been directed to determining whether exercise therapy in the chronic phase of AMI could affect the process of left ventricular remodeling.…”
Section: Nontraining Inferior Groupmentioning
confidence: 99%
“…19 In fact, the degree of left ventricular remodeling is regarded as an important factor in determining the prognosis of MI. [20][21][22] Seals et al reported that left ventricular dilation occurs within hours of AMI in both inferior and anterior AMI, but is more marked in the latter because it has usually more extensive myocardial damage compared with inferior AMI. 23 Moreover, considerable attention has been directed to determining whether exercise therapy in the chronic phase of AMI could affect the process of left ventricular remodeling.…”
Section: Nontraining Inferior Groupmentioning
confidence: 99%
“…A number of other controlled trials also demonstrated that early treatment with captopril after myocardial infarction inhibited left ventricular remodelling, as demonstrated by statistically significant attenuation of left ventricular systolic and diastolic volume expansion [35][36][37][38] and changes in expansion index, thinning ratio, [37] anterior segment length [39] and ejection fraction.l3 4 ] © Adis International Limited. Similar results were noted in a double-blind study of 77 patients receiving 3 months of treatment with captopril 100 mg/day or placebo starting 24 to 48 hours after Q-wave myocardial infarction.l 34 ] While left ventricular volume indices increased markedly among placebo recipients, they were decreased or only modestly increased with captopril, and the difference between treatment groups was statistically significant.…”
Section: Early Treatmentmentioning
confidence: 99%